Pengaruh penggunaan media sosial youtube terhadap motivasi belajar matematika dan self-efficacy siswa menggunakan kurikulum merdeka belajar pada siswa kelas X di SMK Negeri Kota Medan - Saragih, Jenri Hamonangan; Panjaitan, Dedy Juliandri (Mahesa Research Center, 2023)
A curriculum is a plan that guides teaching and learning process activities. The Merdeka Curriculum is a curriculum with diverse extracurricular learning where the content will be more optimal so that students have enough time to deepen concepts and strengthen competencies. This research aims to measure whether there is an influence of YouTube learning media on students' mathematics learning motivation and self-efficacy. This research was conducted using a mixed method by providing questionnaires and instrument questions to research subjects using multiple regression analysis tests. The research results show that there is an influence of using YouTube learning media on student learning motivation by 57.9% and the influence of using YouTube learning media on student self-efficacy is 46.6%. There is an influence of using YouTube learning media on student learning motivation and self-efficacy. is 63.2%.